Method for producing iron ore pellets
By performing the decrystallization water treatment and crushing process of low-quality iron ore, the particle size distribution of ore powder is controlled, and the problem of both the cracking and strength of iron ore pellets is solved, and the stability and yield of the pellets are improved.
Patent Information
- Application Number
- CN202380061039.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-01
- Filing Date
- 2023-05-10
- Publication Date
- 2025-04-04
AI Technical Summary
The prior art is difficult to both inhibit the cracking of iron ore pellets and improve their strength, especially when low-quality ores are used.
The iron ore with an iron component content of 63% by mass is subjected to decrystallization water treatment. The specific steps include heating the iron ore to 100°C to 800°C and maintaining it for 5 minutes to 200 minutes, then crushing the dehydrated ore to obtain ore powder, and controlling the proportion of the particle size of 10 μm or less by sieving is between 10 mass and 70 mass.
It is achieved to increase the strength of iron ore pellets while suppressing collapse, ensuring the stability and yield of the pellets in the firing process.
Smart Images

Figure BDA0005279283660000071 
Figure BDA0005279283660000081 
Figure BDA0005279283660000091
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing iron ore pellets. Background Art
[0002] In the reduction of the shaft furnace method, which is the mainstream of direct reduction ironmaking, lump ore and pellets are used as the raw materials for the furnace. Pellets are produced by the processes of ore crushing, mixing, granulation and firing. In this production process, the iron ore pellets before firing (so-called green pellets) need to have a certain degree of strength to prevent disintegration and pulverization caused by operations such as transportation from the granulation process to the firing process.
[0003] It is known that the control of the strength of green pellets is important to control the particle size of the ore powder after pulverization. If the proportion of fine powder increases, the strength of the green pellets increases. In addition, it is known that during the firing process, the green pellets explode and pulverize due to the evaporation of water in the green pellets, which is known as a phenomenon called collapse, which reduces the yield.
[0004] For example, Japanese Patent Publication No. 04-099132 (Patent Document 1) discloses a method for producing pellets of iron ore containing a large amount of crystal water. In this method, the raw material iron ore containing a large amount of crystal water is crushed and granulated, and then a firing step is added after each step of drying, dehydration and preheating to produce the fired pellets. Before a part or all of the raw material iron ore is crushed, at least a part of the crystal water in the raw material iron ore is dehydrated in advance. It is believed that in this method, the collapse is reduced and the crushing strength of the preheated pellets is increased, thereby achieving an improvement in the product yield.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 04-099132 Summary of the invention
[0008] At present, the raw material ore (iron ore) of pellets generally uses high-quality ore with less crystal water. However, as the demand for high-quality ore increases in the future, it is expected that it will become difficult to ensure the stability of high-quality ore. Therefore, it is considered to use low-quality ores with an iron content (total Fe content) of 63% by mass or less produced in Australia, India, etc. If the crystal water in the iron ore pellets (green pellets) increases, it is easy to collapse as described above, so it is hoped that the improvement of the manufacturing method of the pellets that can suppress the collapse.
[0009] In the pellet manufacturing method of Patent Document 1, if the ore is not dehydrated at an appropriate treatment temperature and time, the crystal water cannot be appropriately reduced. However, in the pellet manufacturing method of Patent Document 1, such appropriate treatment temperature and time are not considered. In addition, excessive dehydration treatment will deteriorate the crushing property of the ore, making it difficult to control the appropriate particle size in the crushing process, and sometimes it is difficult to ensure the strength of the iron ore pellets. Therefore, it is desirable to provide a method for manufacturing iron ore pellets that can take into account both the suppression of collapse and the strength of the iron ore pellets.
[0010] The present disclosure has been made in view of the actual situation, and an object of the present disclosure is to provide a method for producing iron ore pellets that achieves both suppression of collapse and strength of iron ore pellets.
[0011] In order to achieve the above-mentioned object, the method for producing iron ore pellets according to the present disclosure is as follows.
[0012] [1] A method for producing iron ore pellets, comprising a dehydration treatment step of removing crystal water from iron ore having an iron content of 63% by mass or less to obtain dehydrated ore,
[0013] In the de-crystallization water treatment step, the iron ore is heated to 100° C. to 800° C. and maintained for 5 to 200 minutes.
[0014] The method for producing the iron ore pellets according to the present disclosure may also be as follows.
[0015] [2] The method for producing iron ore pellets according to [1] above, wherein:
[0016] The method further comprises a pulverizing step of pulverizing the dehydrated ore to obtain ore powder,
[0017] The proportion of the ore powder having a particle size of 10 μm or less obtained by sieving is 10% by mass to 70% by mass.
[0018] [3] The method for producing iron ore pellets according to [2] above, wherein the proportion of the particles having a particle size of 10 μm or less is 25% by mass to 60% by mass.
[0019] [4] The method for producing iron ore pellets according to [2] or [3] above, wherein the proportion of the particles having a particle size of 10 μm or less is 25% by mass to 60% by mass.
[0020] [5] The method for producing iron ore pellets according to any one of [1] to [4] above, wherein the iron ore has a crystal water content of 3.0% by mass or more.
[0021] According to the method for producing iron ore pellets disclosed in the present invention, it is possible to provide a method for producing iron ore pellets that achieves both suppression of collapse and strength of iron ore pellets. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a graph showing the relationship between the strength of green pellets and the proportion of particles with a diameter of 10 μm or less in ore powder.
[0023] Figure 2 This is a graph showing the relationship between the passing ratio of pellet fragments of green pellets and the ratio of particles with a diameter of 10 μm or less in ore powder. DETAILED DESCRIPTION
[0024] A method for producing iron ore pellets according to an embodiment of the present disclosure will be described.
[0025] First, the outline of the method for producing the iron ore pellets involved in the present embodiment is described. The iron ore pellets involved in the present embodiment are so-called green pellets (pellets before firing). The method for producing the iron ore pellets involved in the present embodiment includes a dehydration treatment step of removing crystal water from iron ore (so-called low-quality ore) having an iron content of 63% by mass or less to obtain dehydrated ore. In the following description, the iron ore having an iron content of 63% by mass or less is referred to as iron ore.
[0026] In the de-crystallization water treatment step, the iron ore is heated to 100° C. to 800° C. and maintained for 5 to 200 minutes.
[0027] The method for producing iron ore pellets further includes a pulverizing step of pulverizing the dehydrated ore to obtain ore powder. In the pulverizing step, the ore powder may be pulverized so that the proportion of particles with a particle size of 10 μm or less is 10% to 70% by mass.
[0028] According to the method for producing iron ore pellets according to the present embodiment, it is possible to achieve both suppression of collapse and strength of iron ore pellets.
[0029] It should be noted that the collapse is a phenomenon in which the green pellets (green pellets) explode and pulverize due to evaporation of water in the green pellets when the iron ore pellets (green pellets) are heated.
[0030] Hereinafter, the method for producing iron ore pellets according to the present embodiment will be described in detail.
[0031] In the method for manufacturing iron ore pellets involved in the present embodiment, in addition to the above-mentioned de-crystallization water treatment step and pulverization step, a granulation step of granulating ore powder to obtain iron ore pellets (green pellets) may be further included. Then, the green pellets are fired in a firing step to become fired pellets. In the following description, due to the difference between the pellets before and after firing, the iron ore pellets involved in the present embodiment (pellets before firing) are sometimes referred to as green pellets, and the pellets after firing are referred to as fired pellets. Green pellets and fired pellets may contain raw materials other than iron ore (e.g., bentonite).
[0032] The type and composition (ore composition) of the iron ore as the raw material of green pellets are not particularly limited. The raw material of green pellets may be a raw material composed of a single iron ore or a raw material obtained by mixing a plurality of ores in any composition.
[0033] The crystal water content of the iron ore (before the crystal water removal step) as the raw material of the green pellets is not particularly limited. The crystal water content can be measured as the weight loss (LOI: Loss On Ignition) of the iron ore when the iron ore is kept at 1000°C for 30 minutes.
[0034] The dehydration treatment step is a step of performing a dehydration treatment to remove crystal water from the iron ore to obtain dehydrated ore. In the dehydration treatment step, the iron ore is heated as a dehydration treatment to remove crystal water from the iron ore.
[0035] In the de-crystallization water treatment process, as the above-mentioned de-crystallization water treatment, the iron ore is heated to a de-crystallization water treatment temperature of 100°C to 800°C and maintained. In this de-crystallization water treatment, the holding time (hereinafter referred to as the de-crystallization water time) of the iron ore at a temperature in the above-mentioned temperature range is 5 minutes to 200 minutes. In the case where the de-crystallization water time is less than 5 minutes, it may not be possible to fully separate the crystal water from the iron ore. In addition, in the case where the de-crystallization water time is greater than 200 minutes, the crushing property of the iron ore may deteriorate. In these cases, the strength of the green pellets may decrease. Therefore, the de-crystallization water time is set to 5 minutes to 200 minutes.
[0036] The dehydration time is preferably 180 minutes or less. If the dehydration time is 180 minutes or less, a decrease in the strength of the green pellets can be appropriately avoided.
[0037] In the de-crystallization water treatment process, the de-crystallization water treatment temperature and the de-crystallization water time are important factors for removing the crystal water. When the de-crystallization water treatment temperature is less than 100°C, the crystal water cannot be fully removed from the iron ore. In addition, when the de-crystallization water treatment temperature is higher than 800°C, the crushing property of the iron ore deteriorates and the strength of the green pellets is insufficient. Therefore, the de-crystallization water treatment temperature is set to 100°C to 800°C. If the de-crystallization water treatment temperature is within this range and the de-crystallization water time is 5 minutes to 200 minutes as described above, it is possible to take into account both the suppression of cracking and the strength of the green pellets.
[0038] The de-crystallization water treatment temperature is preferably 200° C. to 500° C. When the de-crystallization water treatment temperature is within this range, the strength of the green pellets can be sufficiently increased and the collapse can be more effectively suppressed.
[0039] The content of crystal water of the dehydrated ore is also not particularly limited. The content of crystal water of the dehydrated ore is the same as the content of crystal water of the iron ore before the crystal water removal step, and can be measured as LOI. The content of crystal water of the dehydrated ore is preferably reduced by 10% by mass or more than the content of crystal water of the iron ore before the crystal water removal step.
[0040] The pulverizing step is a step of pulverizing the dehydrated ore to obtain ore powder. In the present embodiment, the pulverizing method of the dehydrated ore in the pulverizing step and the pulverizing time required for pulverizing are not particularly limited. When the dehydrated ore powder is pulverized in a batch process, the pulverizing time is preferably 15 minutes to 75 minutes.
[0041] The shape of the ore powder is not particularly limited. For example, it is preferred that the proportion of ore powder particles of 300 μm or less is 95% by mass or more.
[0042] In the particle size distribution of the ore powder, the proportion of particles with a diameter of 10 μm or less may be 10% to 70% by mass. The particle size or particle size distribution of the ore powder is an important factor affecting the strength of the green pellets. It should be noted that the ore powder can be obtained by pulverizing iron ore. The method for pulverizing iron ore is not particularly limited.
[0043] In the particle size distribution of ore powder, the proportion of fine powder with a particle size of less than 10 μm has a great influence on the strength of green pellets. In the particle size distribution of ore powder, when the proportion of fine powder with a particle size of less than 10 μm is less than 10% by mass, green pellets with sufficient strength may not be obtained.
[0044] The reason why the collapse may not be suppressed when the proportion of fine powder with a particle size of less than 10 μm is greater than 70% by mass in the particle size distribution of the ore powder is not clear. However, the following reasons are speculated. That is, in the particle size distribution of the ore powder, if the proportion of fine powder is too much, the structure of the green pellet becomes dense. Therefore, the diffusion path of the crystal water separated by the heat during firing (the flow path from the inside of the green pellet to the outside of the pellet) becomes smaller. As a result, the pressure inside the green pellet is easily increased due to the vaporized water. Therefore, in the particle size distribution of the ore powder, when the proportion of fine powder with a particle size of less than 10 μm is greater than 70% by mass, the collapse may not be suppressed.
[0045] In the particle size distribution of the ore powder, the proportion of fine powder having a particle size of 10 μm or less is preferably 20% to 60% by mass. This can achieve appropriate green pellet strength while suppressing breakage.
[0046] The granulation step is a step of granulating the ore powder to obtain iron ore pellets (green pellets). The granulation method in the granulation step is not limited. In the granulation step, for example, the ore powder can be granulated using a granulator. As a granulator, for example, a disk-type granulator (so-called disk granulator) can be used.
[0047] In the present embodiment, the shape and size (e.g., particle size, average particle size) of the iron ore pellets are not particularly limited and can be any value. The size of the green pellets can be measured, for example, using a vernier caliper to measure the major axis diameter and the minor axis diameter, and the average value thereof is used as the particle size of the green pellets for evaluation. The particle size of the green pellets is preferably 9 mm to 16 mm, which is commonly used in the technical field.
[0048] Then, the green pellets are subjected to a calcining step and calcined to form calcined pellets. The calcining temperature in the calcining step is, for example, 1200°C to 1350°C.
[0049] In the method for producing iron ore pellets according to the present embodiment, when the de-crystallization water treatment temperature and the de-crystallization water time are within the above ranges, the pellets have the strength generally required in the technical field (e.g., 1.0 kg / pellet or more). The strength of the green pellets may preferably be 1.0 kg / pellet or more. In the method for producing iron ore pellets according to the present embodiment, when the particle size distribution of the ore powder as the raw material is a prescribed distribution, that is, when the proportion of particles with a particle size of less than 10 μm is 10% to 70% by mass, the strength of the green pellets tends to be further improved. It should be noted that the strength of the green pellets can be measured using the method described in the examples described later.
[0050] In addition, in the method for producing iron ore pellets according to the present embodiment, if the de-crystallization water treatment temperature and the de-crystallization water time are within the above ranges, the collapse can be suppressed. In the method for producing iron ore pellets according to the present embodiment, further, when the particle size distribution of the ore powder as the raw material is within the above-specified distribution, the collapse can be better suppressed.
[0051] As described above, bursting is a phenomenon in which green pellets burst and pulverize due to the evaporation of water in the iron ore in the green pellets when the green pellets are heated. The ease with which the bursting occurs, i.e., the bursting property, can be evaluated, for example, based on the proportion of pellets of 5 mm or less produced after the green pellets are heated at a specified temperature (e.g., 300°C) or after the green pellets are fired. In detail, when the bursting occurs during the firing process or when the green pellets are heated at a specified temperature (hereinafter referred to as the firing process, etc.), the green pellets burst or pulverize, and fine (e.g., 5 mm or less) pellet fragments are produced. Therefore, if the amount of pellet fragments produced in the firing process, etc. is large, bursting is likely to occur (high bursting property), and from the perspective of suppressing bursting, it can be evaluated as not good. On the contrary, if the amount of pellet fragments produced in the firing process, etc. is small, bursting is not likely to occur (low bursting property), and from the perspective of suppressing bursting, it can be evaluated as good.
[0052] If the amount of pellet fragments generated during the firing process is 3.0 mass % or less, preferably 1.5 mass % or less, and more preferably 1.0 mass % or less, the yield rate of the fired pellets can be suppressed from decreasing. Therefore, if the amount of pellet fragments generated during the firing process is 1.0 mass % or less, it can be evaluated as high-quality green pellets with suppressed cracking.
[0053] Example
[0054] Green pellets were produced according to the following procedure and the disintegration properties were evaluated.
[0055] As the iron ore (raw ore) used as the raw material of green pellets, ores (Ore A, Ore B) having the chemical composition shown in Table 1 were used. It should be noted that, as described above, "LOI" in Table 1 represents the content (mass %) of crystal water. In addition, in Table 1, "T.Fe" represents the mass % of the iron content (total Fe content) in the iron ore. It should be noted that "T.Fe" is a value quantified by the total iron quantification method of iron ore specified in JIS M 8212:2022. As shown in Table 1, Ore A and Ore B, which are raw materials for green pellets, are both iron ores having a T.Fe of 63% or less (so-called low-quality ores).
[0056] [Table 1]
[0057]
[0058] Table 2 shows information on the ore used for the green pellets (ore properties), conditions or evaluation results of the dehydration treatment process, the pulverization process, the granulation process, and the calcination process. Hereinafter, the green pellets of Experiment Nos. 1 to 16 were obtained by using the ore blends shown in Table 2 through the dehydration treatment process, the pulverization process, the granulation process, and the calcination process described later.
[0059]
[0060] Each raw material ore prepared according to the ore mixing ratio shown in Table 2 was subjected to a dehydration treatment at the dehydration treatment temperature and dehydration time shown in Table 2 to obtain a dehydrated ore (dehydration process). The dehydration treatment was performed in the air. As the crystal water content of the dehydrated ore, the LOI of the dehydrated ore is shown in Table 2.
[0061] Next, the dehydrated ore was pulverized using a ball mill for the pulverization time shown in Table 2 (batch processing) to obtain ore powder (pulverization step). Then, the proportion of fine powder with a particle size of 10 μm or less in the ore powder was measured as the passing ratio (mass %) of a sieve with a mesh size of 10 μm obtained by sieving. In Table 2, the proportion of fine powder with a particle size of 10 μm or less in the ore powder is expressed as the "-10 μm ratio" in the pulverization step.
[0062] In Table 3, the particle size distribution of the ore powder is expressed as the cumulative 10% diameter (D10), cumulative 50% diameter (D50: median diameter) and cumulative 90% diameter (D90) based on volume. These cumulative 10% diameter, cumulative 50% diameter and cumulative 90% diameter are derived from the volume-based particle size distribution in the ore powder measured using a laser diffraction particle size analyzer (Mastersizer 3000 manufactured by Malvern). It should be noted that the dispersion medium used in measuring the particle size distribution is water. For ease of reading, the same "-10μm ratio" as in Table 2 is listed again in Table 3.
[0063] [Table 3]
[0064]
[0065] Next, 1.0 mass % of bentonite is added to the ore powder to obtain a mixed powder. It should be noted that bentonite is added as a binder during granulation, but it is not necessary in the present embodiment. The mixed powder is granulated using a disc-type granulator (Pelletizer) to obtain green pellets (granulation step). During granulation, water is added to the mixed powder while the mixture is rolled in such a manner that the granulation moisture (amount of water added) is 10 mass % to 10.5 mass % of the weight of the green pellets. It should be noted that the granulation moisture can be determined by measuring the weight change of the green pellets before and after they are kept at 105°C for 24 hours. For example, when the weight change ratio of the green pellets after being kept at 105°C for 24 hours is minus 10 weight %, the granulation moisture is 10%.
[0066] The particle size of the green pellets was measured using a vernier caliper to measure the major axis diameter and the minor axis diameter, and the average value (arithmetic mean) was used. It should be noted that for each experimental No., the particle sizes of 10 green pellets were measured, and their average value (arithmetic mean) was used as the particle size of the green pellets of the experimental No.
[0067] The strength of the green pellets was measured using an Autograph. The strength of the green pellets was measured by deforming the green pellets at a displacement speed of 1 mm / min and obtaining a load-displacement curve. The load corresponding to the peak position of the first displacement in the load-displacement curve was used as the strength of the green pellets. For each experimental No., the strength of 10 green pellets was measured, and their average value (arithmetic mean) was used as the strength of the green pellets of the experimental No.
[0068] The disintegration property is evaluated by the amount of pellet fragments produced after the firing process. Specifically, the disintegration property is evaluated as follows. First, 500 g of green pellets are placed in a vertical furnace (cylindrical with a diameter of 60 mm), and 300°C air is ventilated from the bottom of the green pellet layer to the top at a wind speed of 1.0 m / sec (converted to 300°C / 1 atmospheric pressure) for 10 minutes. Next, the green pellets exposed to the 300°C air are heated to 1250°C in another electric furnace other than the above-mentioned furnace, and then fired at this temperature for 25 minutes (firing process). Then, the green pellets are taken out of the furnace, sieved with a sieve with a mesh of 5 mm, and the passing ratio (mass %) of the pellet fragments passing through the sieve is measured as an evaluation of the disintegration property. In Table 2, the passing ratio of the pellet fragments is expressed as "-5 mm ratio".
[0069] As shown in Table 2, for the green pellets of Experiments No. 1 to 5, 8 to 14, 17 and 18, in which the de-crystallization water treatment temperature was 100°C to 800°C and the de-crystallization water time was 5 minutes to 200 minutes, the strength was 1.0 kg / pellet or more. In addition, for the green pellets of these Experiments No., the passing ratio of pellet fragments (-5 mm ratio), which is an index of disintegration, was 3.0 mass % or less, specifically, 1.5 mass % or less. That is, the green pellets of these Experiments No. involved in this embodiment have both strength and disintegration of the green pellets.
[0070] It should be noted that in the production process of green pellets in these experiments No. 1 to 5, 8 to 14, 17 and 18, the content of crystal water of the dehydrated ore (LOI of the dehydrated ore) was reduced by 14% by mass or more in the dehydrated ore treatment process compared with the content of crystal water of the iron ore (raw material ore) before the dehydrated ore process (LOI of the raw material ore). Compared with experiments No. 6 and 15 in which both the strength and the disintegration property of the green pellets were not taken into consideration, it is considered that the content of crystal water of the dehydrated ore is preferably reduced by 10% by mass or more than the content of crystal water of the iron ore before the dehydrated ore process.
[0071] As shown in the green pellets of Experiments No. 1 to 5, 8 to 14, 17 and 18, even if the content of crystal water of the iron ore before the de-crystallization process is 4.9 mass % or more, the strength and disintegration of the green pellets can be taken into account. Therefore, when the content of crystal water of the iron ore before the de-crystallization process is less than 4.9 mass %, for example, 3.0 mass % or more, as long as the de-crystallization treatment temperature is 100°C to 800°C and the de-crystallization time is 5 minutes to 200 minutes, it can be considered that the strength and disintegration of the green pellets can be taken into account. It should be noted that for high-quality ores used in the previous direct reduction ironmaking method, the content of crystal water is mostly about 1.0 mass % or less. In addition, for iron ore pellets used in blast furnaces, the most (maximum) is the use of iron ore with a crystal water content of less than 3.0 mass %.
[0072] In addition, among the green pellets of Experiments No. 1 to 5, 8 to 14, 17 and 18, the green pellets of Experiments No. 1 to 5, 10 to 14, 17 and 18, in particular, the green pellets of Experiments No. 1 to 5, 10 to 14, 17 and 18, in which the proportion of particles with a diameter of 10 μm or less (-10 μm proportion) in the ore powder was 10 mass % to 70 mass %, all had a particularly good ratio of 1.0 mass % or less in terms of the passing ratio of pellet fragments (-5 mm ratio), which is an index of disintegration. In addition, the green pellets of these Experiments No. were also excellent in that the strength of the green pellets was higher than that of the green pellets of Experiments No. 8 and 9, in which the proportion of particles with a diameter of 10 μm or less (-10 μm proportion) in the ore powder was not 10 mass % to 70 mass %.
[0073] In addition, when the green pellets of Experiments Nos. 1 to 5, 10 to 14, 17 and 18 are compared with the green pellets of Experiments Nos. 8 and 9, it can be seen that the strength of the green pellets is easily improved when D90 is 50 μm to 200 μm.
[0074] It should be noted that for the green pellets of Experiments No. 6 and 7 in which the de-crystallization water treatment temperature was not 100° C. to 800° C. and the de-crystallization water treatment time was not 5 minutes to 200 minutes, the strength of the green pellets was less than 1.0 kg / pellet or the passing ratio of pellet fragments (-5 mm ratio) was greater than 1.0% by mass. That is, the green pellets of Experiments No. 6, 7, 15 and 16 could not achieve both the strength and the disintegration property of the green pellets.
[0075] Figure 1 The relationship between the strength of the green pellets of Experiments Nos. 1 to 5, 8 to 14, 17 and 18 and the proportion of particles with a diameter of 10 μm or less (-10 μm proportion) in the ore powder is shown in FIG. Figure 2 The relationship between the passing ratio of pellet fragments (-5 mm ratio) of the green pellets of Experiments Nos. 1 to 5, 8 to 14, 17 and 18 and the ratio of particles with a diameter of 10 μm or less (-10 μm ratio) in the ore powder is shown in FIG.
[0076] according to Figure 1 As shown in the coordinate graph, if the proportion of particles with a diameter of 10 μm or less (-10 μm proportion) in the ore powder is 10% to 70% by mass, the strength of the green pellet is 1.0 kg / pellet or more. In particular, if the proportion of particles with a diameter of 10 μm or less in the ore powder is 25% to 60% by mass, it can be clearly seen that the strength of the green pellet is further improved. Figure 1 As shown by the solid line in the graph, as the proportion of the particle size of 10 μm or less in the ore powder moves from the smaller side to the larger side, the strength of the green pellets is generally convex upward.
[0077] according to Figure 2 As shown in the graph, if the proportion of particles with a diameter of 10 μm or less (-10 μm proportion) in the ore powder is 10% to 70% by mass, the proportion of pellet fragments passing through (-5 mm proportion) is 1% or less by mass. Figure 2 As shown by the dotted line, as the proportion of the particle size of 10 μm or less in the ore powder moves from the small side to the large side, the passing ratio of the pellet fragments is generally convex downward.
[0078] right Figure 1 , Figure 2By comparing the figures of FIG. 1 and FIG. 2 , it can be said that, in general, when the proportion of particle sizes below 10 μm (-10 μm proportion) in the ore powder is 25% to 60% by mass, the strength of the pellets is particularly high, the passing ratio of pellet fragments is also steadily reduced, and the collapse is well suppressed, so it is particularly preferred.
[0079] As described above, a method for producing iron ore pellets can be provided.
[0080] It should be noted that the embodiments disclosed in this specification are illustrative only, and the embodiments of the present disclosure are not limited thereto, and can be appropriately modified within the scope not departing from the purpose of the present disclosure.
[0081] Industrial Applicability
[0082] The present disclosure is applicable to a method for producing iron ore pellets.
Claims
1. A method for producing iron ore pellets, comprising a dehydration treatment step of removing crystal water from iron ore having an iron content of 63% by mass or less to obtain dehydrated ore, In the de-crystallization water treatment step, the iron ore is heated to 100° C. to 800° C. and maintained for 5 to 200 minutes.
2. The method for producing iron ore pellets according to claim 1, wherein: The method further comprises a pulverizing step of pulverizing the dehydrated ore to obtain ore powder, The proportion of the ore powder having a particle size of 10 μm or less obtained by sieving is 10% by mass to 70% by mass.
3. The method for producing iron ore pellets according to claim 2, wherein: The ratio of the particles with a diameter of 10 μm or less is 25% by mass to 60% by mass.
4. The method for producing iron ore pellets according to claim 2 or 3, wherein: The cumulative 90% diameter in the volume-based particle size distribution of the ore powder is 50 μm to 200 μm.
5. The method for producing iron ore pellets according to any one of claims 1 to 4, wherein: The iron ore has a crystal water content of 3.0 mass % or more.
Citation Information
Patent Citations
Production of pellet of iron ore containing much water of crystallization
JP1992099132A